1999
DOI: 10.1007/pl00013850
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Resource Allocation of Six Plantago Species with Different Breeding Systems

Abstract: Species of Plantago exhibit great deal of differences in the breeding system. The reproductive effort calculated on the basis of, (i) dry biomass of foliar and floral parts and (ii) seed output-weight (mg) per unit leaf area (cm2), exhibits relation with breeding system. The predominantly inbreeding taxa invest higher reproductive effort compared to their outbreeding allies. In terms of sex allocation strategies, the outbreeding species like f . lamlafa, f , lasopus invest more to the development of floral fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…These changes would have been equally important, however, as long-lived perennials should allocate more resources to tissue maintenance, whereas short-lived annuals should allocate more resources to reproduction. A few studies (Pitelka 1977;Abrahamson 1979;Primack 1979;Sharma et al 1999) support the notion that a shift in resource allocation accompanies the transition between annuality and perenniality, but these studies are based on biomass measurements and provide limited information about how the energy invested into a particular tissue is being spent.…”
Section: Introductionmentioning
confidence: 90%
“…These changes would have been equally important, however, as long-lived perennials should allocate more resources to tissue maintenance, whereas short-lived annuals should allocate more resources to reproduction. A few studies (Pitelka 1977;Abrahamson 1979;Primack 1979;Sharma et al 1999) support the notion that a shift in resource allocation accompanies the transition between annuality and perenniality, but these studies are based on biomass measurements and provide limited information about how the energy invested into a particular tissue is being spent.…”
Section: Introductionmentioning
confidence: 90%
“…Pollen production per anther is varied with accounts ranging from 11 908 + 262.2 (average + s.d.) grains [24] to as many as 20 500 + 2200 [20]. On average, each grain has a mass of 14.…”
Section: Biology Of Plantago Lanceolatamentioning
confidence: 99%
“…He found that, even if this trade-off is considered, resource allocation to the female functions increases with an increase in the self-fertilization rate. Several empirical data agree with this hypothesis (Charnov 1987, McKone 1987, Morgan andBarrett 1989, Schoen 1982, Sharma et al, 1999). However, sex allocation in these species is female-biased even in predominantly outcrossing populations or a variety, and hence self-fertilization alone cannot explain female-biased sex allocation in these species (but see McKone 1987).…”
Section: Mw I Wi)># M I Wi) For All (F M)#(fw Mw)mentioning
confidence: 54%